Comparative analysis of digital health insurance platform adoption among urban–rural users: A UTAUT and financial literacy integration perspective - Anni Wei; Yurita Yakimin Abdul Talib; Zakiyah Sharif (Digital Health)
Objective The aim of this study is to compare the determinants of digital health insurance platform adoption among urban and rural users. The study incorporates a financial literacy (FL) perspective in the unified theory of acceptance and use of technology (UTAUT) model to explore the effect of FL on users’ adoption intentions. Methods This study used a cross-sectional research design, utilising a sample of 389 urban and 323 rural users familiar with digital health insurance platform. Furthermore, this study employed partial least squares multi-group analysis (PLS-MGA) to examine the path differences between urban and rural groups. Results The results revealed some differences in the factors that shape the willingness of urban and rural users to adopt digital health insurance platforms. Performance expectancy (PE), effort expectancy (EE), social influence (SI), and FL positively affect the adoption intentions of rural and urban users. However, facilitating conditions only positively affect rural users’ adoption intentions. Regarding the moderation effect, FL strengthens the effect of PE on adoption intentions for both urban and rural users. Interestingly, FL shows differences moderating role between urban and rural users in the relationship between EE and SI on adoption intentions. Implication By introducing a FL perspective, this study addresses the lack of attention to FL in Insurtech studies. It provides a theoretical basis for the government and platform operators in formulating differentiated promotion strategies to help increase the popularity of health insurance in urban and rural areas.